Ammonium based dicationic ionic liquids: An interaction with CRABP I deciphered with biophysical perspective - Pratyush Ranjan Hota; Devi Prasanna Behera; Harekrushna Sahoo (Journal of Ionic Liquids)
The present article examined the impact of ammonium-based dicationic ionic liquids (ILs) as co-solvent on the biophysical behaviour of CRABP I protein using various spectroscopic techniques along with molecular docking to support the experimental outcomes. Fluorescence study revealed significant alternations in the microenvironments of aromatic fluorescent amino acid residues. Fluorescence intensity indicated a decline upon increase in concentration of co-solvents, with a red shift. A similar trend also observed with the synchronous study. Stern-Volmer parameters revealed the static quenching behaviour whereas, existence of electrostatic interaction between protein and ILs is revealed from binding study using temperature-dependent fluorescence measurements. Conformational and structural changes of the protein were analysed using Circular Dichroism spectrometer. Molecular docking study supported the spectroscopic outcomes at the molecular level.